CBX4 contributes to HIV‐1 latency by forming phase‐separated nuclear bodies and SUMOylating EZH2. (1st June 2022) - Wu, Liyang; Pan, Ting; Zhou, Mo; Chen, Tao; Wu, Shiyu; Lv, Xi; Liu, Jun; Yu, Fei; Guan, Yuanjun; Liu, Bingfeng; Zhang, Wanying; Deng, Xiaohui; et al.
Abstract: The retrovirus HIV‐1 integrates into the host genome and establishes a latent viral reservoir that escapes immune surveillance. Molecular mechanisms of HIV‐1 latency have been studied extensively to achieve a cure for the acquired immunodeficiency syndrome (AIDS). Latency‐reversing agents (LRAs) have been developed to reactivate and eliminate the latent reservoir by the immune system. To develop more promising LRAs, it is essential to evaluate new therapeutic targets. Here, we find that CBX4, a component of the Polycomb Repressive Complex 1 (PRC1), contributes to HIV‐1 latency in seven latency models and primary CD4 + T cells. CBX4 forms nuclear bodies with liquid–liquid phase separation (LLPS) properties on the HIV‐1 long terminal repeat (LTR) and recruits EZH2, the catalytic subunit of PRC2. CBX4 SUMOylates EZH2 utilizing its SUMO E3 ligase activity, thereby enhancing the H3K27 methyltransferase activity of EZH2. Our results indicate that CBX4 acts as a bridge between the repressor complexes PRC1 and PRC2 that act synergistically to maintain HIV‐1 latency. Dissolution of phase‐separated CBX4 bodies could be a potential intervention to reactivate latent HIV‐1. Synopsis: Polycomb group protein CBX4 recruits EZH2 on the HIV‐1 promoter and SUMOylates EZH2 within CBX4 bodies, which promotes HIV‐1 latency via a liquid–liquid phase separation‐dependent mechanism. The polycomb protein CBX4 contributes to HIV‐1 latency in seven latency models and primary CD4 + T cells. CBX4 forms nuclear bodies with liquid–liquid phase separation characteristics. CBX4 SUMOylates EZH2 to promote H3K27me3 catalytic activity. The phase separation properties of CBX4 play key roles in EZH2 SUMOylation and HIV‐1 latency. Abstract : Polycomb group protein CBX4 recruits EZH2 on the HIV‐1 promoter and SUMOylates EZH2 within CBX4 bodies, which promotes HIV‐1 latency via a liquid–liquid phase separation‐dependent mechanism.